The Role of Adiponectin in the Protective Action of Dietary Saturated Fat Against Alcoholic Fatty Liver in Mice - You, Min (2005)
The protective effect of dietary saturated fatty acids against the development of alcoholic liver disease has long been known, but the underlying mechanism is incompletely understood. Here we examined the involvement of the adipocyte hormone adiponectin. Circulating adiponectin levels were significantly elevated by chronic ethanol administration to mice consuming a high saturated fat diet. The increase in circulating adiponectin was associated with the activation a set of hepatic signaling pathways mediated through AMPK, PPARα, and PGC-1α, which in turn led to markedly increased rates of fatty acid oxidation, prevention of hepatic steatosis, and alleviation of liver enzyme changes. Furthermore, treatment of rat 3T3-L1 adipocytes with saturated fatty acids (palmitic or stearic acids) in the presence of ethanol increased secretion of adiponectin and enhanced activity of a mouse adiponectin promoter. In conclusion, the protective action of saturated fat against the development of alcoholic fatty liver in mice is partially mediated through induction of adiponectin. The present findings suggest a novel paradigm for dietary fatty acids in the pathogenesis of alcoholic liver disease, and provide a promising therapeutic strategy, which is nutritional modulation of adiponectin, in treating human alcoholic fatty liver disease.